Mellan produktion och bevarande: Hållbart skogsbruk som diskursiv konstruktion i svensk skogsdebatt - Steiner Blasberg,Sara (2025)
The Swedish forestry debate is deeply polarised concerning the issue of the meaning and implications of sustainable forestry. This study explores how competing discourses on sustainability are constructed within the Swedish forestry debate and which actors contribute to their articulation and dissemination. Drawing on Maarten Hajer’s argumentative discourse analysis (ADA), the paper identifies dominant storylines surrounding the concept of sustainable forestry and applies the concept of discourse coalitions to understand how actors align based on shared discursive patterns rather than formal collaborations. The analysis shows that the bioeconomy discourse – by integrating elements from limits to growth, ecological modernisation, and neoliberal discourses – functions as a unifying narrative that reconciles otherwise competing perspectives on sustainable forestry. Three main storylines are identified: (1) sustainable growth through strong ownership rights, (2) the expanding bioeconomy that combines economic growth and environmental protection within the existing political-economic system, and (3) the need for systemic transformation to ensure that the forestry remains within planetary and social boundaries. The debate is structured around two primary discourse coalitions: the production coalition and the conservation coalition. The findings show that the production coalition achieves discursive dominance by framing sustainability as compatible with economic growth and positioning forestry as a climate solution.
Keywords: Argumentativ diskursanalys (ADA); Svensk skogsdebatt; Hållbart skogsbruk; Skogsutredningen 2019; Bioekonomi